Searching for the simplest self-assembling dendron to study helical self-organization and supramolecular polymerization. (December 2022) - Peterca, Mihai; Sahoo, Dipankar; Imam, Mohammad R.; Xiao, Qi; Percec, Virgil
Highlights: First generation self-assembling dendron. Helical supramolecular column from achiral and chiral structure. Helical self-organization and supramolecular polymerization. 5/1 helical. Abstract: The first generation self-assembling dendron (4Bp-3, 4)nG1CO2 CH3 where Bp is biphenyl, n is an achiral linear, n -dodecyl, or branched chiral alkyl group, ( S )-3, 7-dimethyl-octyl (dm8*) undergoes helical self-organization in bulk state and in solution. The supramolecular columns assembled from this dendron are helical, regardless, if the alkyl groups on its periphery are achiral or chiral. This demonstrates self-organization of helical columns both from achiral and chiral dendrons and reveals that the role of the stereocenter is to select the helical sense of an already helical column. This very simple self-assembling dendron can be subjected to a large diversity of chemical modifications and functionalization, all expecting to maintain the helical function in bulk and in solution in the range of temperature of interest to investigate helical self-organization and supramolecular polymerization. Graphical abstract: Image, graphical abstract